2019
DOI: 10.1089/tmj.2018.0023
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Telehealth Administration Protocol for the NIH Toolbox-Cognition Battery

Abstract: Our novel videoconference protocol for the NIHTB-CB is equivalent to the standard protocol in healthy participants, and may provide a solution for researchers seeking to engage study participants at remote sites. If the NIHTB-CB is used longitudinally to monitor patients, corrections for repeated measures may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This encompasses the majority of measures we have selected for use ( Table 1 ), and includes measures such as paragraph and word list learning tasks [ [54] , [55] , [56] , [57] ], verbal span/working memory tasks (such as digit span) [ [54] , [55] , [56] , [57] ], verbal fluency tasks [ [54] , [55] , [56] , [57] , [58] ], and measures of crystallized intelligence (e.g. measures of word reading and vocabulary [ [57] , [58] , [59] , [60] ]). There is also evidence for tasks that rely upon verbal responses to visually presented stimuli, such as visual confrontation naming [ 54 , 55 ] and visuoperceptual reasoning tasks (e.g.…”
Section: Practical Considerations For Telenpmentioning
confidence: 99%
“…This encompasses the majority of measures we have selected for use ( Table 1 ), and includes measures such as paragraph and word list learning tasks [ [54] , [55] , [56] , [57] ], verbal span/working memory tasks (such as digit span) [ [54] , [55] , [56] , [57] ], verbal fluency tasks [ [54] , [55] , [56] , [57] , [58] ], and measures of crystallized intelligence (e.g. measures of word reading and vocabulary [ [57] , [58] , [59] , [60] ]). There is also evidence for tasks that rely upon verbal responses to visually presented stimuli, such as visual confrontation naming [ 54 , 55 ] and visuoperceptual reasoning tasks (e.g.…”
Section: Practical Considerations For Telenpmentioning
confidence: 99%
“…Under certain conditions, such as during an epidemic, it might be preferable to administer a cognitive screening remotely instead of in-person, even with the obvious disadvantages of reduced patient contact and control over the test setting. Other cognitive test batteries, such as the NIH Toolbox-Cognition, have adapted their test protocols for remote administration (Rebchuk et al, 2019). Mindmore is fully self-administrative and as such requires little adaptation to be performed in a remote setting (Owens et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the aforementioned novel digital tests have also been adapted for telehealth administration. The NIH toolbox has been administered using videoconferencing and showed no significant difference to in-person testing [43]. Cogstate has not published any data on remote protocols, but a study on their digital battery (in-clinic but unsupervised) demonstrated no significant differences between unsupervised and supervised scores [44 ▪ ].…”
Section: Remote Testingmentioning
confidence: 99%